Microglial repopulation alleviates age-related decline of stable wakefulness in mice - Liu, Hanxiao; Badawy, Mohamed; Sun, Shaoqin; Cruz, George; Ge, Shaoyu; Xiong, Qiaojie (Frontiers in Aging Neuroscience, 2022)
Changes in wake/sleep architecture have been observed in both aged human and animal models, presumably due to various changes throughout the aging body particularly in the brain. Microglia have emerged as a modulator for wake/sleep architecture in the adult brain, and displayed changed morphology and activity in the aging brain. However, the link between microglia and aging-related wake/sleep changes remains elusive. In this study, we systematically examined the brain vigilance and microglia morphological changes in aging mice, and determined how microglia affect the aging-related wake/sleep change in mice. We found that from young adult to aged mice there was a clear decline in stable wakefulness at nighttime, and a decrease of microglial processes length in various brain regions involved in wake/sleep regulation. Stable wakefulness decreased and restored following the time course of microglia depletion and repopulation in the adult brain. Microglia repopulation in the aging brain restored age-related decline in stable wakefulness. Together our findings suggest a potential link between aged microglia and wake/sleep change in aged brains.